Disciplining deserving subjects through social assistance : migration and the diversification of precarity in Singapore - Ye, Junjia (2020)
Cities are not only associated with incommensurable human diversity but also play a pivotal role in generating, assembling, and mobilizing differences. Alongside neoliberal processes that drive migrant-led diversification in global cities, we are witnessing growing inequality and precarity in populations of long-term residents that are themselves heterogeneous. Indeed, the diversification of peoples in the global city is also paralleled by the diversification of precarity. Yet, the ways in which new configurations of difference are producing more nuanced if still shadowy subjects of citizenship deserve more conceptual and contextualized attention. Although much has been written on the management of migration, far less attention has been focused on the management of multiplying forms of precarity resulting from insecure sociolegal status, disadvantaged labor market position, and deeply inscribed social prejudice. Even less has been documented on how these forms of management set up specific vernaculars about and subjects of citizenship, migrancy, and precariousness. This article addresses social inequality and the relationality of subject making in the context of diversification in Singapore, a city-state that has a particular historical understanding of diversity through a fixed formulaic “multiracialism.” Drawing on state narratives and interview data, we analyze organized social support for both migrants and citizens both by state organizations and nongovernmental organizations to demonstrate the limits and possibilities of change and continuity in the production of precarity in the diversifying city. In doing so, we aim to extend scholarship of the global city beyond the well-debated issue of social polarization in the global city and to highlight the diversity and relationality of precariousness in a contemporary non-Western global city.